2017
DOI: 10.3390/molecules22040623
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailable Citrus sinensis Extract: Polyphenolic Composition and Biological Activity

Abstract: Citrus plants contain large amounts of flavonoids with beneficial effects on human health. In the present study, the antioxidant and anti-inflammatory potential of bioavailable polyphenols from Citrus sinensis was evaluated in vitro and ex vivo, using the murine macrophages cell line J774A.1 and primary peritoneal macrophages. Following simulated gastro-intestinal digestion, the in vitro bioavailability of Citrus sinensis polyphenolic extract was assessed using the human cell line Caco-2 grown as monolayers on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 38 publications
2
30
0
2
Order By: Relevance
“…In particular, in the hydro-alcoholic extract of orange smoothie, 22 polyphenols and 4 limonoids glycosides were identified. In accordance with our previous results [8,16], the most abundant compounds were the flavanone narirutin and hesperidin. However, narirutin content was higher in smoothies than fresh juice.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In particular, in the hydro-alcoholic extract of orange smoothie, 22 polyphenols and 4 limonoids glycosides were identified. In accordance with our previous results [8,16], the most abundant compounds were the flavanone narirutin and hesperidin. However, narirutin content was higher in smoothies than fresh juice.…”
Section: Discussionsupporting
confidence: 93%
“…The methanolic extract was able to reduce macrophages pro-inflammatory mediators and different cytokines. Furthermore, Citrus sinensis polyphenols have been shown to have antioxidant effect by reducing reactive oxygen species (ROS) and increasing cytoprotective enzymes expression [16]. In this regard, in the present study, we evaluated the ability of Vitis vinifera and Citrus sinensis smoothies, and relative mixes, to inhibit and counteract the doxorubicin-induced oxidative stress in embryonic rat heart-derived cells (H9c2).…”
Section: Introductionmentioning
confidence: 99%
“…Analyses were performed in direct infusion following a previous protocol [ 33 , 38 ] employing a Hamilton syringe (250 μL) at a flow rate of 2 μL/min. Data were acquired on a SolariX XR 7T (Bruker Daltonics, Bremen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…16 The sweet orange (Citrus sinensis L. Osbeck) can have a wide range of benecial effects on health. 17,18 Sweet orange juice contains potent bioactive compounds including avonoids (hesperidin and narirutin, predominantly as glycosides), carotenoids (xanthophylls and carotenes), vitamin C and other benecial phytochemicals. It has been reported that sweet orange juice (OJ) consumption may be associated with potential health benets.…”
Section: Introductionmentioning
confidence: 99%